2022
DOI: 10.1128/jvi.00958-22
|View full text |Cite
|
Sign up to set email alerts
|

The Glycan-Binding Trait of the Sarbecovirus Spike N-Terminal Domain Reveals an Evolutionary Footprint

Abstract: Spike N-terminal domains (S-NTD) of sarbecoviruses are highly diverse; however, their function remains largely understudied compared with the receptor-binding domains (RBD). Here, we show that sarbecovirus S-NTD can be phylogenetically clustered into five clades and exhibit various levels of glycan binding in vitro .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Binding between proteins and cells was detected by a Dylight 650 labeled goat anti-human IgG Fc antibody (Abcam, ab98622). For pseudotyped particles binding assay, the pseudotypes were generated as described above and purified through ultracentrifugation as previously described ( 57 ). The purified pseudotyped particles were incubated with Huh-7 cells at 4°C for 1 h before fixation by 4% PFA and permeabilization by PBS plus 0.25% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Binding between proteins and cells was detected by a Dylight 650 labeled goat anti-human IgG Fc antibody (Abcam, ab98622). For pseudotyped particles binding assay, the pseudotypes were generated as described above and purified through ultracentrifugation as previously described ( 57 ). The purified pseudotyped particles were incubated with Huh-7 cells at 4°C for 1 h before fixation by 4% PFA and permeabilization by PBS plus 0.25% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…51 Glycosylations act as shields against the host immune response, as mutations in glycosites can alter antibody susceptibility by sterically hindering access to antibody binding sites. 16,38 Structure-guided glycosome studies can provide insights into antibody evasion or evolutionary history. For example, NTD glycosite N96 and RBD glycosite N344 are conserved in all three SARSr-CoVs, but are not observed in SARS-CoV-2 (7E7B), suggesting that the civet and bat SARSr-CoVs may be more resistant to antibodies that recognize this region.…”
Section: Discussionmentioning
confidence: 99%
“…In all these glycoproteins N2, N3 and N5 loops are shorter than in RaTG13, consistent with research showing large variations in NTD length across the sarbecovirus family, indicating frequent loop remodeling. [36][37][38][39][40][41][42]…”
Section: Structural Conservation Amongst Sarsr-cov Glycoproteinsmentioning
confidence: 99%
“…A characterization of glycan binding capability of spike‐NTD from betacoronaviruses of non‐human hosts revealed that the spike‐NTDs engaged uncharacterized glycan‐conjugated molecules in vitro and depletion of sialic acids from host cells enhanced viral entry, suggesting that SARS‐related coronaviruses retained glycan‐binding in their NTDs. However, such interaction did not contribute to viral entry 89 . Understanding glycobiology in non‐human hosts and the biology of SARS‐related viruses will shed light on the function of these conserved galectin‐like NTDs in defining host tropism, cross‐species transmission and viral infectivity.…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%
“…However, such interaction did not contribute to viral entry. 89 Understanding glycobiology in non‐human hosts and the biology of SARS‐related viruses will shed light on the function of these conserved galectin‐like NTDs in defining host tropism, cross‐species transmission and viral infectivity. It will aid early detection and prevention of spill events that may cause future pandemics.…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%